Clasificador de objetos por reflectividad - Loor, Gonzalo (2010)
This project aims to demonstrate an application of the Scorbot robotic arm in the industry. It is an application developed in the laboratory using the Scorbot robotic’s software and use cube-shaped objects of different colors that are fetched after sliding down a ramp and activate the limit switch sensor that sends the signal to start the sequence of robot, Taking first action in their claws and approaching the object at various distances from a photoelectric sensor that is activated at different distances depending on the degree